Joubert syndrome: accuracy of neuro-radiological findings - Lingawi, Sattam S.; Arab, Nahla A.; Fahmy, Yasser Ragab (Journal of Pediatric Neurology, 2004)
To evaluate the accuracy of neuroimaging in establishing the diagnosis of Joubert syndrome. Computed tomography (CT) and magnetic resonance imaging (MRI) were performed in seven infants/children with the clinical diagnosis of Joubert syndrome. The clinical diagnoses were based on characteristic clinical features. The CT scans were performed on a single detector helical CT scans and the MRI were performed on 1-T and 1.5-T MRI systems. All studies were evaluated for the presence of cerebellar vermian aplasia/hypoplasia, cerebellar hypoplasia, horizontal alignment of the superior cerebellar peduncle, "molar tooth" configuration of the brainstem and "bat wing" appearance of the fourth ventricle. Other neuroimaging abnormalities such as hydrocephalus, dysgenesis of the corpus callosum were also reported. Cerebellar vermian hypoplasia with a midline cleft, horizontal alignment of the superior cerebellar peduncle, "molar tooth" configuration of the brainstem and dilated fourth ventricle with "bat wing" appearance in all patients. Cerebellar hemisphere hypoplasia was seen only in three cases. Brainstem molar tooth sign, fourth ventricular bat wing sign and the horizontal orientation of the superior cerebellar peduncles are characteristic findings Joubert syndrome. (J Pediatr Neurol 2004; 2(1): 33–37).
Keywords: Joubert syndrome; molar tooth sign; vermian hypoplasia